Suicidality Associated With Deep Brain Stimulation in Extrapyramidal Diseases: A Critical Review and Hypotheses on Neuroanatomical and Neuroimmune Mechanisms - Costanza, Alessandra (Front Integr Neurosci, 2021)
Deep brain stimulation (DBS) is a very well-established and effective treatment for patients with extrapyramidal diseases. Despite its generally favorable clinical efficacy, some undesirable outcomes associated with DBS have been reported. Among such complications are incidences of suicidal ideation (SI) and behavior (SB) in patients undergoing this neurosurgical procedure. However, causal associations between DBS and increased suicide risk are not demonstrated and they constitute a debated issue. In light of these observations, the main objective of this work is to provide a comprehensive and unbiased overview of the literature on suicide risk in patients who received subthalamic nucleus (STN) and internal part of globus pallidum (GPi) DBS treatment. Additionally, putative mechanisms that might be involved in the development of SI and SB in these patients as well as caveats associated with these hypotheses are introduced. Finally, we briefly propose some clinical implications, including therapeutic strategies addressing these potential disease mechanisms. While a mechanistic connection between DBS and suicidality remains a controversial topic that requires further investigation, it is of critical importance to consider suicide risk as an integral component of candidate selection and post-operative care in DBS.